Resistotypes as a characterization of microbial communities associated with human health. Systematic Review - Alexander V. Pavlenko; Ignat V. Sonets; Aleksandr I. Manolov; Elizaveta V. Starikova; Elena N. Ilina (Журнал микробиологии, эпидемиологии и иммунобиологии, 2025)
The concept of resistotype represents a new characterization of bacterial communities distinct from their taxonomic composition. The term “resistotype” is now commonly used to refer to specific clusters within a resistome that possess a characteristic phenotypic profile, or set of antimicrobial resistance genes. In contrast to traditional approaches that focus on individual resistance genes or phenotypic manifestations of resistance, resistome analysis allows resistance to be considered at a more comprehensive level, integrating different genes and their interactions within microbial populations or an entire microbial community.